ANALISIS SISTEM INFORMASI AKUNTANSI PEMBELIAN (STUDI PRAKTIK KERJA PT TATASOLUSI PRATAMA SURABAYA) - BERNADIEN KRISTIA DEVI (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
The accounting system is a means for management to obtain information that will be used to manage the company and to prepare financial statements for the parties concerned. Internal control is a technique that can help leaders to achieve corporate objectives as well as a useful means to secure the resources or the price of the company’s assets, check accuracy and correctness of accounting data, anagement policies have been implemented. Accounting information system is a good purchase must be accompanied by effective internal controls. PT. Tatasolusi Pratama Surabaya has been able to apply the accounting information system is very adequate to be able to create an effective internal control. Although there are some drawbacks, such as the procedures for distributing documents is uneven and there is duplication between the functions of reception function with the storage function, but with the optimization on a healthy practice, this can be resolved quite well by the company.